HUBUNGAN ASUPAN VITAMIN D DENGAN KADAR SERUM 25 (OH) D PADA IBU HAMIL TRIMESTER III - Nurhikmah Asyari; Aminuddin; Nasruddin AM (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2020)
Food Frequency Questionnaire (FFQ) is a questionnaire used to find out the number of frequencies and amounts of portion sizes of food and beverages consumed in a certain period of time, generally either in a day, a month or a year, especially in pregnant women. In fulfillment of this nutrient used serum levels of 25 (OH) D to see the results of vitamin D needs in pregnant women who will be good for the mother and her fetus.  This study aims to find out the relationship of intake needs of vitamin D using Food Frequency Questionnaire with serum levels of 25 (OH) D in pregnant women Trimester III. The type of research used is descriptive analytics with cross-sectional study. The population in this study was all pregnant women in trimester III who visited Antenatal Care (ANC), the number of samples as many as 62 pregnant women trimester III. This research was conducted in Makassar City in November – December 2019. Uji statistics show that there is no significant relationship between intake of vitamin D needs using Food Frequency Questionnaire (FFQ) with serum levels of 25 (OH) D in pregnant women Trimester III (p >0.05). Cross tabulation data showed that mothers who had OH (D) serum deficiency tended to have adequate intake of vitamin D intake, pregnant women who were insufficiency and serum sufficiency OH (D) tended not to have enough intake of vitamin D intake.